2021
DOI: 10.3390/plants10020318
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Uses and Applications of Moringa oleifera in Bakery Products

Abstract: Moringa oleifera belongs to the Moringaceae family and is the best known of the native Moringa oleifera genus. For centuries, it has been used as a system of Ayurvedic and Unani medicine and has a wide range of nutritional and bioactive compounds, including proteins, essential amino acids, carbohydrates, lipids, fibre, vitamins, minerals, phenolic compounds, phytosterols and others. These characteristics allow it to have pharmacological properties, including anti-diabetic, anti-inflammatory, anticarcinogenic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 74 publications
3
53
0
1
Order By: Relevance
“…According to the literature, several studies have shown that saponins can induce the lyses of erythrocytes [71,73], such as iridoids, which constitute the main cause of the hemolysis observed when using the n-BuOH and EtOAc extracts of S. stellata. In addition, iridoid glycosides cause hemolytic anemia and a decrease in red blood cells and hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, several studies have shown that saponins can induce the lyses of erythrocytes [71,73], such as iridoids, which constitute the main cause of the hemolysis observed when using the n-BuOH and EtOAc extracts of S. stellata. In addition, iridoid glycosides cause hemolytic anemia and a decrease in red blood cells and hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Green aerial parts from E. camaldulensis var obtusa and M. piperita were separately hydrodistillated for 3 h via a Clevenger unit to extract the essential oils (EOs) [33]. The obtained EOs were kept dry in Eppendorf tube and stored at 4 • C in a refrigerator.…”
Section: Preparation and Chemical Analyses Of The Natural Oilsmentioning
confidence: 99%
“…The seeds are resistant to rancidity because they contain powerful antioxidants that act as natural preservatives [32]. The oil from the seeds can be used as a fertiliser in plantations to encourage the growth of other species [33], and it is also used as an edible coating to increase the shelf life of certain vegetables and fruit [34].…”
Section: Introductionmentioning
confidence: 99%
“…The action mechanism proposed for the inhibitory ability of flavonoids is associated with the number of hydroxyl groups on the B ring of the flavonoid skeleton, the formation of hydrogen bonds between the hydroxyl groups of the polyphenol ligands, and the catalytic residues of the binding site of the enzyme [ 68 ]. The important inhibitory ability is noticed in flavonols and flavones groups [ 68 , 69 , 70 ]. Our finding is in agreement with the preceding ones; the EamCE has presented an impressive antidiabetic activity that was more efficient than the one of acarbose, and we have noted a very large difference comparing their IC 50 (µg/mL): 22.66 ± 0.17, 3650.93 ± 10.70, respectively.…”
Section: Discussionmentioning
confidence: 99%